Aged neuronal nitric oxide knockout mice show preserved olfactory learning in both social recognition and odor-conditioning tasks - James, Bronwen M.; Li, Qin; Luo, Lizhu; Kendrick, Keith M. (Frontiers in Cellular Neuroscience, 2015)
There is evidence for both neurotoxic and neuroprotective roles of nitric oxide (NO) in the brain and changes in the expression of the neuronal isoform of nitric oxide synthase (nNOS) gene occur during aging. The current studies have investigated potential support for either a neurotoxic or neuroprotective role of NO derived from nNOS in the context of aging by comparing olfactory learning and locomotor function in young compared to old nNOS knockout (nNOS/-) and wildtype control mice. Tasks involving social recognition and olfactory conditioning paradigms showed that old nNOS-/-animals had improved retention of learning compared to similar aged wildtype controls. Young nNOS-/- animals showed superior reversal learning to wildtypes in a conditioned learning task, although their performance was weakened with age. Interestingly, whereas young nNOS-/- animals were impaired in long term memory for social odors compared to wildtype controls, in old animals this pattern was reversed, possibly indicating beneficial compensatory changes influencing olfactory memory may occur during aging in nNOS-/- animals. Possibly such compensatory changes may have involved increased NO from other NOS isoforms since the memory deficit in young nNOS-/-animals could be rescued by the NO-donor, molsidomine. Both nNOS-/- and wildtype animals showed an age-associated decline in locomotor activity although young nNOS-/- animals were significantly more active than wildtypes, possibly due to an increased interest in novelty. Overall our findings suggest that lack of NO release via nNOS may protect animals to some extent against age-associated cognitive decline in memory tasks typically involving olfactory and hippocampal regions, but not against declines in reversal learning or locomotor activity.